2022
DOI: 10.3390/toxins14110729
|View full text |Cite
|
Sign up to set email alerts
|

Current Review of Mycotoxin Biodegradation and Bioadsorption: Microorganisms, Mechanisms, and Main Important Applications

Abstract: Mycotoxins are secondary metabolites produced by fungi. Food/feed contamination by mycotoxins is a great threat to food safety. The contamination can occur along the food chain and can cause many diseases in humans and animals, and it also can cause economic losses. Many detoxification methods, including physical, chemical, and biological techniques, have been established to eliminate mycotoxins in food/feed. The biological method, with mycotoxin detoxification by microorganisms, is reliable, efficient, less c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 180 publications
0
10
0
Order By: Relevance
“…However, enzymatic degradation is complex, and the potential safety of secondary metabolites produced during toxin degradation must be evaluated to bring biodegradation methods into practical application. 9,10 The first and most widely studied ZEN-degrading enzyme is ZEN lactone hydrolase, breaking the lactone bond of ZEN to produce a nonestrogenic degradation product. 11 After ZHD101, many hydrolases were identified, some of which have exceptional characteristics.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, enzymatic degradation is complex, and the potential safety of secondary metabolites produced during toxin degradation must be evaluated to bring biodegradation methods into practical application. 9,10 The first and most widely studied ZEN-degrading enzyme is ZEN lactone hydrolase, breaking the lactone bond of ZEN to produce a nonestrogenic degradation product. 11 After ZHD101, many hydrolases were identified, some of which have exceptional characteristics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Enzymatic degradation is free of several limitations associated with the use of live organisms for detoxification, enhancing safety and specificity. However, enzymatic degradation is complex, and the potential safety of secondary metabolites produced during toxin degradation must be evaluated to bring biodegradation methods into practical application. , …”
Section: Introductionmentioning
confidence: 99%
“…13,14 In contrast, enzymatic degradation offers advantages, including mild reaction conditions, high efficiency, low cost, and convenient operations. 15,16 Fungal laccases (EC 1.10.32) have attracted considerable attention due to their environmentally friendly characteristics and catalytic properties, such as high oxidation−reduction potentials, wide temperature ranges, and maximum activity under acidic conditions. 17,18 These characteristics make them suitable for use in food and feed environments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Conventional detoxification methods for mycotoxins involve physical, chemical, and microbial approaches. , However, these methods possess drawbacks such as nutrient loss, reagent residues, and secondary pollution to the environment. , In contrast, enzymatic degradation offers advantages, including mild reaction conditions, high efficiency, low cost, and convenient operations. , Fungal laccases (EC 1.10.32) have attracted considerable attention due to their environmentally friendly characteristics and catalytic properties, such as high oxidation–reduction potentials, wide temperature ranges, and maximum activity under acidic conditions. , These characteristics make them suitable for use in food and feed environments . To date, several studies have reported the efficiency of laccases from fungi and bacteria in degrading AFB 1 and ZEN.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the scientific fraternity has been working on the designing of electrochemical biosensors for the recognition of mycotoxins. Till now, a number of reviews on the presence of mycotoxins in various food and feed products, their health impacts, and their biological degradation are available [ 9 , 10 , 11 , 12 ]. A few reviews on current methods of detection of mycotoxins are also available.…”
Section: Introductionmentioning
confidence: 99%